Comparative pharmacokinetics and absolute bioavailabilities of two enrofloxacin generic preparations after single intracrop bolus administrations to broiler chickens - Ehmeza, Nasser; Elmajdoub, Abdelrazzag; El-Mahmoudy, Abubakr (International Journal of Pharmacology and Toxicology, 2016)
The pharmacokinetics and absolute bioavailabilities of two generics of enrofloxacin (ENRO) 10% oral solution formulation at a dose of 10 mg/Kg body weight were compared after single intracrop (i.c.) bolus administrations in reference to single intravenous (i.v.) standard ENRO administration in broilers using a randomized parallel design. The two tested formulations were Enrol® (Medmac®, Amman, Jordan) as ENRO-A and Syvaquinol® (Syva®, Leon, Spain) as ENRO-B 10% oral solutions. An HPLC assay using pure ENRO base as a standard was used to measure concentrations of ENRO from the selected sources in plasma collected at predetermined time points up to 24 hours. The pharmacokinetic analysis of the C-T data was performed using non-compartmental analysis based on statistical moment theory with the help of computerized WinNonlin program (Version 5.3, Pharsight® Corporation, St. Louis, USA). The maximum plasma concentrations (Cmax) for ENRO-A and ENRO-B were 1.61 ± 0.203 and 1.79 ± 0.283 μg/mL, respectively, attained at time to peak (Tmax) of 2 h. Elimination half-lives (t1/2β) were 8.391 ± 0.312 and 8.458 ± 0.906 h, respectively. While areas under plasma concentration-time curves (AUC0-∞), and systemic bioavailabilities (F) were 12.744 ± 2.951 and 14.354 ± 2.85 mg.h/L; and 78.96 ± 6.728 and 88.94 ± 10.89 % for ENRO-A and ENRO-B, respectively. It could be concluded that despite the superior pharmacokinetic profile of ENRO-B over ENRO-A, however, both generics were within the FDA and EMA bioequivalence acceptance range of 80%–125% and thus can be used as interchangeable therapeutic agents in chickens.